Extinction of a conditioned response in rainbow trout selected for high or low responsiveness to stress - Moreira, PSA; Pulman, KGT; Pottinger, T. G. (Elsevier B.V., 2004)
Two lines of rainbow trout (Oncorhynchus mykiss) that exhibit divergent endocrine responsiveness to stressors also display disparate behavioral traits. To investigate whether the high-responding (HR) and low-responding (LR) fish also differ in cognitive function, the rate of extinction of a conditioned response was compared between the two lines. Groups of HR and LR fish were exposed to a paired conditioned stimulus (CS- water off) and unconditioned stimulus (US; confinement stressor). After exposure to 18 CS-US pairings, at least 70% of individuals of both lines acquired a conditioned response (CR) manifested as an elevation of blood cortisol levels on presentation of the CS only. Post-conditioning, the fish were tested by presentation of the CS at weekly intervals, for 4 weeks, with no further reinforcement, and the extinction of the CR in the two lines was compared. The decline in mean plasma cortisol levels after exposure to the CS over successive tests suggested that the CR was retained for a shorter period among the HR (<14 days) than LR fish (<21 days). The frequency of individuals within each line whose plasma cortisol levels indicated a stress response when exposed to the CS was significantly greater among the LR than HR fish at 14 and 21 days with no HR fish falling into this category at 21 days. At 28 days post-conditioning, there were no HR fish and only three LR fish were categorized as stressed. These results suggest that there are differences in cognitive function between the two lines. Possible mechanisms underlying these differences are discussed. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: conditioning; stress response; cortisol; behavior; rainbow trout; selective breeding; Oncorhynchus mykiss